Western Scholarship and the Islamic Resurgence in the Arab World (American Journal of Islam and Society, 1993)
During the last two decades, the politics of certain Arab countrieshave been influenced by various Islamic groups. Some of these groupshave expressed their dissatisfaction with the performances of theirgovernments by Using the available political channels to seek change;others have resorted to violence. Armed protests have taken the form ofbombings, assassinations, and mass demonstrations.Suicide attacks and armed struggle took place against Israeli, American,and French forces in Lebanon (1982-83). President Sadat of Egyptwas assassinated in 1981 by Egyptian military pemnnel who were membersof an Islamic movement. Another armed struggle against the Syrianregime was initiated by the Syrian Islamic Front in 1976-82. Numerousdemonsttations against the governments of Morocco, Algeria, and Tunisiatook place during the 1980s.Other Muslim groups attempted to participate in the decision-makingprocess in their countries. The Society of Muslim Brothers in Egypt encouragedits prominent members to run for election to the Egyptian Parliament.However, the Society was not considered a legal party accordingto Egyptian law. The Wafd, a legitimate party, allowed the Society ofMuslim Brothers to campaign under their banner. As a result, membersof the Society voted in accordance with their ideological and political beliefsrather than the Wafd party line. In Jordan, the Society of MuslimBrothem campaigned as an independent party during the 1988 electionsand won twenty percent of the seats.Due to the Arab countries’ economic and strategic importance, variousgovemments, scholars, and private and public organizations have paid closeattention to these incidents. In an attempt to understand this phenomenon,academic conventions have been held, books and articles have been published,and gmnts have been awarded for research. Western and Arabscholars have described it with such labels as Islamic fundamentalism,revivalism, awakening, reformism, resurgence , renewal, militancy, or simply ...